Adhesion of filamentous fungi isolated from drinking water under different process conditions - Fernandes, Susana (2019)
Filamentous fungi (ff) are consistently recognized as drinking water (DW) inhabitants, typically harboured in biofilms. Their sessile behaviour is still poorly understood. This study aimed the evaluation of the influence of several abiotic factors (substratum, hydrodynamic conditions and nutrient availability) on biofilm formation by Penicillium brevicompactum and P. expansum isolated from DW. Fungal adhesion was quantified on high density polyethylene (HDPE) and polyvinyl chloride (PVC) surfaces using synthetic tap water (STW) and R2A broth, under stagnant or agitated (25 and 150?rpm) conditions. Fungal spore numbers were assessed after staining with Calcofluor White MR2 and epifluorescence microscopy. The surface charge and physicochemical properties of spores were characterized for a mechanistic understanding on the adhesion process. The adhesion kinetics of spores was represented accurately by the Logistic model, in which adhesion increased with time until a maximum level attained before spore germination (8?h after incubation). In general, P. brevicompactum demonstrated to adhere in a higher extent than P. expansum (12?×?104 spores/cm2 vs 1.7?×?104 spores/cm2). Moreover, fungal adhesion was potentiated under stagnation and using R2A broth. HDPE and PVC allowed spore adhesion at similar extents. Adhesion predictions based on the extended Derjaguin, Landau, Verwey and Overbeek (XDLVO) theory corroborated the experimental results, highlighting the role of physicochemical surface properties on the adhesion of spores. These results allowed to refine a model for ff biofilm formation. The overall results help to understand key aspects determining the presence of P. brevicompactum and P. expansum biofilms in DW, where stagnant conditions and the presence of nutrients should be avoided to prevent ff biofilm formation.